Exploration of the advantages of minimally invasive surgery for clinical T4 colorectal cancer compared with open surgery: A matched-pair analysis. Issue 32 (12th August 2022) - Imaizumi, Ken; Homma, Shigenori; Miyaoka, Yoichi; Matsui, Hiroki; Ichikawa, Nobuki; Yoshida, Tadashi; Takahashi, Norihiko; Taketomi, Akinobu
Abstract : The indications of minimally invasive surgery (MIS) for T4 colorectal cancer are controversial because the advantages of MIS are unclear. Therefore, we compared overall survival (OS) and recurrence-free survival (RFS) as the primary endpoint, and short-term outcome, alteration in perioperative laboratory data, and the interval of postoperative chemotherapy from operation as secondary endpoints, between MIS and open surgery (OPEN) using a matched-pair analysis. We explored the advantages of MIS for T4 colorectal cancer. In this retrospective single-institution study, we included 125 patients with clinical T4 colorectal cancer who underwent curative-intent surgery of the primary tumor between October 2010 and September 2019. Conversion cases were excluded. MIS patients were matched to OPEN patients (ratio of 1:2) according to tumor location, clinical T stage, and preoperative treatment. We identified 25 and 50 patients who underwent OPEN and MIS, respectively, including 31 with distant metastasis. Both groups had similar background characteristics. The rate of major morbidities (Clavien-Dindo grade > III) was comparable between the 2 groups ( P = .597), and there was no mortality in either group. MIS tended to result in shorter postoperative hospitalization than OPEN ( P = .073). Perioperative alterations in laboratory data revealed that MIS suppressed surgical invasiveness better compared to OPEN. Postoperative chemotherapy, especially for patients with distant metastasis who underwent primary tumor resection, tended to be started earlier in the MIS group than in the OPEN group ( P = .075). OS and RFS were comparable between the 2 groups ( P = .996 and .870, respectively). In the multivariate analyses, MIS was not a significant prognostic factor for poor OS and RFS. MIS was surgically safe and showed similar oncological outcomes to OPEN—with the potential of reduced invasiveness and enhanced recovery from surgery. Therefore, patients undergoing MIS might receive subsequent postoperative treatments earlier.